Revival to revolution: medieval narratives in Irish republicanism - Brinkman-Schwartz, C (2023)
Medieval narratives that had been celebrated in the Gaelic Revival (c.1880-1916) became a tool of republican self-fashioning in the revolutionary era (c.1912-23). As revolutionary nationalism developed into a movement distinct from Revivalism, it acquired its own flavour of engagement with medieval history and literature. This project argues for the continued cultural relevance of medieval narratives throughout the revolutionary period. Employing a hybrid methodology and incorporating a wide range of source material, this study adds nuance to our understanding of the transition from Revival to Revolution. The project demonstrates that medieval narratives not only remained a part of revolutionary culture after the Rising, but were selected, reimagined and deployed in ways specific to this context.